On the Structure of Strelau Temperament Inventory (STI) - Tadinac, Meri (Array, 1989)
The aim of this study was to determine the internal factor structure of the Strelau Temperament Inventory (STI). STI was administered to a sample of 494 high school students. Threee types of analyses were carried out: a) the common factor analysis applied on the item correlation matrix ; b) the confirmatory factor analysis and the comparable restricted exploratory analysis based on 18 composite variabels, obtained by dividing each scale into several subscales (equivalent tests) on the basis of the STI content analysis ; c) the unrestricted exploratory analysis of 18 composite variables. Although the claim is made that STI measures three dimensions, according to the analyses done, it contains four factors. The results show only a partial correspondence between the extracted factors and the STI scales in terms of their content. There are considerable indications that the STI measures three basic nervous system properties, but in such a way that it purports to do.